Cognitive Architecture to Analyze the Effect of Intrinsic Motivation with Metacognition over Extrinsic Motivation on Swarm Agents - Ashwini Kodipalli (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This research work describes the setup of framework for testing the performance of intrinsically motivated swarm agents over extrinsic motivation. The performance is tested through the simulation. The result demonstrates that agents with intrinsic motivation for specific goal have high metacognitive ability. It also shows group performance of agents with metacognitive ability is better than the group of agents with extrinsic motivation exhibiting cognitive ability. Goal setting theory of motivation is applied to the group of agents in order to analyse the intelligent behaviour of the agents. This research is mainly focusing on why and how group performance by swarm agents is better than individuals. This approach requires design of ambient testbed where swarm agents demonstrate cognitive actions to metacognitive actions. This research is aiming to prove that group performance by swarm agents is higher due to type of agents chosen with intrinsic motivation and thus proves intrinsic motivation is better than extrinsic motivation. Agent behaviour in a group can be analysed using different metrics like resource collection, life expectancy, level of motivation and task assigned.